COMPARATIVE ANALYSIS OF THE ESSENCE AND STRUCTURE OF TRADITIONAL AND NONLINEAR EDUCATIONAL PROCESS IN THE HIGHER SCHOOL - L. I. Vasilyev (Образование и наука)
The need for developing the open nonlinear system of higher education is caused by the structural uncertainty of educational processes, chaotic aspirations of trainees and other disorganizing factors. Such complicated phenomena demanding a new conceptual approach are difficult to explain and manage in the framework of classical pedagogy. In author’s opinion, the conceptual apparatus of synergetics can be used as an instrument for modeling and designing the coherent interaction of subjects in the higher school educational process. The author specifies some categories such as self-organization of the system – a process or number of processes facilitating its self-formation, self-restoration and self-modification.The paper presents the research data concerning the pedagogic content of the main synergetic concepts. A comparative analysis of the essence and structure of traditional (linear) and nonlinear educational process was carried out emphasizing such components as educational goals, content, forms, organizational methods, teaching resources, specifics and content of the teachers and trainees’ activities.The research findings can be used in developing the educational model adapting to the changing socio-cultural environment.